Morphological And Pigmentary Variations Of Tinea Versicolor In South Indian Patients - Ajaykrishnan; Thappa Devinder Mohan (Wolters Kluwer Medknow Publications, 2003)
In general, tinea versicolor is though to cause hypopigmented lesions in individuals with dark skin and hyperpigmented lesions in those with white skin. This view has come under scrutiny and hence we undertook the current study. It was a descriptive study based on a sample size of 100 patients of tinea versicolor, who attended the skin OPD of Jawaharlal Institute of Postgraduate Medical Education, and Research (JIPMER), Pondicherry. These patients were recruited during the peak period. The age of patients ranged from 1 to 88 years with a mean age of 26.25 + 5.23 years. Six cases occurred in children. Majority of cases (59%) occurred in the age group of 15-29 years, followed by 30-44 years (23%) and 45-60 years 45-60 years 990%). There were 81 males and 19 females with male to female ratio of 4.26:1. Trunk especially upper trunk was the predominant site involved (75 cases), followed by neck (45 cases), face (41 cases), upper limb (34 cases) and lower limb (9 cases). Majority of cases had hypopigmented variety). To conclude, from our study, we could say that all types of pigmentary variations in tinea versicolor are present in South Indian patients with a predominance of hypopigmented ones. Moreover, both types of pigmentary anomalies can occur simultaneously in any individual case.